Fast-track development of vaccines for SARS-CoV-2: The shots that saved the world - Chavda, Vivek P.; Yao, Qian; Vora, Lalitkumar K.; Apostolopoulos, Vasso; Patel, Chirag A.; Bezbaruah, Rajashri; Patel, Aayushi B.; Chen, Zhe-Sheng (Frontiers in Immunology, 2022)
In January 2020, the World Health Organisation (WHO) announced a global health emergency and declared a coronavirus disease 2019 (COVID-19) as a pandemic on 11 March 2020, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The spread and severity of the outbreak took a heavy toll and overburdening of the global health system, in particular due to the unavailability of anti-SARS-CoV-2 drug treatment. With an immediate world-wide effort, communication, sharing of data, large amounts of funding, researchers and pharmaceutical companies immediately fast-tracked vaccine development in order to prevent hospitalisations and death. A number of vaccines were quickly approved for emergency use and world-wide vaccination rollouts were immediately put in place. However, due to many individuals being hesitant to receive the vaccine and many poorer countries did not have access to vaccines, multiple SARS-CoV-2 variants quickly emerged which were distinct from the original variant. Uncertainties related to the effectiveness of the various vaccines against the new variants as well as vaccine specific-side effects have remained a concern for the world. Despite these uncertainties, fast-track vaccine approval, manufacturing at a large scale, and the effective distribution of COVID-19 vaccines remain the topmost priorities around the world. Unprecedented efforts taken by vaccine developers/researchers to healthcare staff played a major role in distributing vaccine shots that provide strong protection, against infectious disease, even with the delta and omicron variants. Fortunately, even for those who become infected, vaccination appears to protect against major disease, hospitalisation, and fatality from COVID-19. Herein, we analyse ongoing vaccination studies and vaccine platforms that has saved many deaths from the pandemic.